Exploring factors influencing SMEs’ success: The perspective of entrepreneurial and learning orientations - Sukma, Andhi (Journal of Innovation in Business and Economics, 2024)
The primary objective of this study is to explore the intricate relationship between learning orientation, business strategy, and firm performance among small and medium-sized enterprises (SMEs) in Indonesia. By examining the impacts of innovation, proactiveness, and risk-taking on both business strategy and learning orientation, this research aims to shed light on the factors influencing SME success. Surveys were administered to a purposive sample of 300 SMEs in Jakarta and West Java, and data were analyzed using structural equation modeling. The findings indicate that innovation positively influences both business strategy and learning orientation, whereas proactiveness has a minimal impact on business strategy but significantly affects learning orientation. Furthermore, risk-taking emerges as a crucial driver of both business strategy and learning orientation. This study contributes by providing empirical evidence on the significance of entrepreneurial traits in shaping SME performance and offers practical insights for enhancing organizational sustainability and growth in the Indonesian business context.